Penanaman Karakter melalui Kegiatan Rohani di SD Negeri 3 Pendowo Kranggan Temanggung - M Milati; Hamidulloh Ibda (Institut Islam Nahdlatul Ulama Temanggung, 2020)
Cultivation of character is very important to face the changing times that get the spotlight from the wider community. One way to instill the character of students in Pendowo State Elementary School 3, Kranggan District, Temanggung Regency is through spiritual activities. In this study will discuss about how to inculcate character through spiritual activities in SD Negeri 3 Pendowo. This study aims to describe the planting of student character through spiritual activities in Pendowo State Elementary School 3. This study is a qualitative study using field studies at Pendowo State Elementary School 3. Data collection techniques through observation, interviews. and documentation from various elements of the school elements. And the analysis is done by deductive method which is the concordance between the findings of existing theories and proven by the findings of the data in the field. Based on the results of research conducted by researchers concluded that the planting of student character through Spiritual activities in Pendowo State Elementary School 3by using several methods, namely the Duha prayer, Dhuha prayer in congregation, reading the Koran, the reading of short letters / juz amma, reading Asmaul Husnah , and recitation / culture, and sharing make it possible to change the character of students to behave well.